Los estilos de apego en mujeres con y sin violencia conyugal - Sánchez J., Hugo Manuel (2016)
This study aims to determine the differences in attachment styles between women with and without spousal violence, beneficiaries of soup kitchens in Huacho, where the sample was of 60 women. To this end the relevant study design was descriptive-comparative, and inferential statistical analysis was worked with a significance level of p <0.05. Questionnaire forms of coexistence of Vicuña and Sanchez, and Attachment Styles Scale for romantic and non-romantic relationships of Casullo and Fernandez was applied. It is concluded that there are significant differences in fearful-avoidant style of romantic attachment among women with and without spousal violence, being non-abused women have higher scores.